The constitutionality of the Iraqi Kurdistan Region's Referendum to secede - Sanh Shareef Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The referendum is a mechanism whereby people can give their opinion on the public issues whether on the constitutional, legal or political issues. However, the referendums can be held by the executive or legislative powers or by the president of the state through a constitutional text. Kurdistan region of Iraq (KRI) conducted a referendum on 25 September 2017 by an overwhelming majority vote of roughly 93.25 percent in favour of Kurdistan secession. Therefore, this paper aims to investigate which sort of referendums exercised by Kurdistan Regional Government (KRG), and the constitutionality of the Kurdistan region referendum from the perspective of the Iraqi Constitution. The paper discovers information from secondary sources to cross-examine opinions and reach conclusions. It is concluded that the referendum in the Kurdistan region was a political referendum, therefore its constitutionality can be assumed that imposing the right of self-governance as a law cannot establish a State; it can only occur with the endorsement of the mother State, through a constitutional structure. At the other side, the question of the referendum's constitutionality is essentially a matter of legal controversy, which goes further than the facts of the constitutional framework.